Try again, fail again: Samuel Beckett and the sequel play - Simpson, H (Cambridge University Press, 2021)
Samuel Beckett’s Waiting for Godot has spawned several unauthorized sequel plays, which see Godot arrive on stage in 1960s Yugoslavia, 1980s Ireland, 1990s America, and early 2000s Japan. The sequel play is a largely ignored phenomenon in literary scholarship, with the sequel form itself routinely dismissed as a derivative and inevitably disappointing text. Yet the sequel text also resituates and re-evaluates the original text, and its reiterative nature aptly parallels the paradox of non-ending in Beckett’s original Waiting for Godot. Focusing on four unauthorized stage sequels to Beckett’s play – Miodrag Bulatović’s Godot Has Arrived (Godo je došao, 1966), Alan Titley’s Godot Arrives (Tagann Godot, 1987), Daniel Curzon’s Godot Arrives (1999), and Minoru Betsuyaku’s Godot Has Come (Yattekita Godot, 2007) – this essay examines how these sequels rework the cultural logic of Godot’s arrival to their own critical and political ends. These playwrights draw on the very recursive, even frustrating nature of the sequel form itself as an exegetic framework, reproducing the trope of non-ending that characterizes Beckett’s own work.